Pseudobacteremia outbreak of biofilm-forming Achromobacter xylosoxidans – environmental transmission - Günther, Frank (BMC Infect Dis, 2016)
BACKGROUND: Achromobacter xylosoxidans (AX) is known for intrinsic resistance to disinfectants. Our laboratory routine surveillance system detected an unexpected rise in AX bloodstream infections in a 2200-bed hospital. An epidemiological investigation was conducted to find the source and disrupt further transmission. METHODS: Outbreak cases were defined as patients with at least one positive blood culture positive for AX from May 2014 to May 2015. Medical records were reviewed, affected wards, as well as the microbiology laboratory were audited. Additionally, microbiologic culture and biofilm staining for suspected antiseptic reusable tissue dispensers were performed, and isolated AX strains were typed using RAPD PCR and PFGE. RESULTS: During the outbreak period, AX were isolated from blood cultures from 26 patients. The retrospective cohort study did not reveal common risk factors. The clinical features of the case patients suggested a pseudobacteremia. The reusable tissue dispensers containing Incidin® Plus solution product were found to be contaminated with biofilm-forming AX. Typing of the isolates revealed that blood culture isolates were identical with the strains found in the dispensers. CONCLUSIONS: After changing the usage of the product to single-use and educating staff, the outbreak was terminated. Contamination of dispensers occurred due to insufficient reprocessing, since biofilm disrupting steps were not included in the process.